2017
DOI: 10.18203/2349-2902.isj20173213
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological profile, diagnosis and treatment of skin cancers at a tertiary care center: a retrospective study

Abstract: INTRODUCTIONMalignant skin lesions have become increasingly prevalent over the past several years. In United States, approximately 5.4 million cases of non-melanoma skin cancers are treated in 2012.1 Skin cancer account for more than 40% of all malignancies. Majority of skin cancers are basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and melanoma which account for more than 95% of total skin malignancies. 1The incidence in males in Delhi for malignant melanoma is 0.29% and 0.90% for other skin cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The lowest occurrence of skin cancer according to their study was 2nd decennium and below. (9) Ivan et al also found similar results. In their study higher incidences on skin tumour were in age group 31-40 years and 41-50 years.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The lowest occurrence of skin cancer according to their study was 2nd decennium and below. (9) Ivan et al also found similar results. In their study higher incidences on skin tumour were in age group 31-40 years and 41-50 years.…”
Section: Discussionmentioning
confidence: 59%
“…In their study male to female ratio was 1.9:1. (9) In a consecutive study of four years we found that there were more patients from rural background as compared to urban. Similar results were also present in a study carried out by Kumar et al In their study 76% patients from rural population as compared to urban population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This head and neck region is under direct effect of prolonged sun exposure. [ 10 13 ] Maximum number of our cases ( n = 30, 46%) were farmers and laborers by occupation who worked outdoors for 6-7 hours daily. The rare sites involved in BCC were popliteal fossa and dorsum of hand.…”
Section: Discussionmentioning
confidence: 99%
“…have also found sun exposure as the most common risk factor for development of cutaneous malignancies. [ 10 13 ] The role of environmental factors in the causation of skin cancers has been extensively reviewed. UVB radiation is well known as an agent inducing skin cancers in a dose dependent way.…”
Section: Discussionmentioning
confidence: 99%